The ORGANIZATIONAL CULTURE AS A MODERATOR BETWEEN SELECTED INSTITUTIONAL REFORMS AND CHANGE OF BEHAVIOR OF INMATES. A STUDY OF CORRECTIONAL FACILITIES IN KENYA: ORGANIZATIONAL CULTURE AS A MODERATOR BETWEEN SELECTED INSTITUTIONAL REFORMS AND CHANGE OF BEHAVIOR OF INMATES. A STUDY OF CORRECTIONAL FACILITIES IN KENYA - KOOME, GIKUNDI SOLOMON (Advances in Social Sciences Research Journal, 2020)
This Research focused on organizational culture as a moderator variable between selected institutional reforms and change of behavior of inmates in correctional facilities in Kenya. The objective was to assess the moderating influence of organizational culture on the relationship of selected institutional reforms and change of behavior of inmates in correctional facilities in Kenya. The study tested one alternate hypothesis on whether the relationship among the study variable was significant. The target population was 10,111 individuals spread as 2,953 prison officers and 7,158 inmates. From this population a sample was drawn using a formula totaling to 385 individuals who were picked for the study. Purposive sampling was used to select officers’ in-charge and their deputies. With r=0.747, t=8.558, at p=0.000, 0.05, HI was concluded that the relationship between institutional reforms and change of behavior of inmates is moderated by organizational culture. Findings of the study are expected to clearly demonstrate how continuous quality improvement should be undertaken within correctional facilities.